European refugee crisis : where do public intellectuals stand? - Medeiros, Pilar Damião (2018)
The European refugee crisis has become one of the most puzzling aspects of European society and politics. The continent’s worst humanitarian crisis since World War II has prompted a novel political and social labyrinth. As European leaders struggle to respond to the increasing number of refugees crossing their countries’ borders, divisions tend to become more visible in the public debate. This paper explores the different positions of European public intellectuals: from French intellectuals, such as Finkielkraut, Houellebecq and Onfray, who tend to show sympathy with right-wing Islamophobic populism, to Jürgen Habermas, Zygmunt Bauman, Slavoj Zizek, among others, who appeal to relieve the refugee emergency. Whereas some still condemn war and imperialism, oppression and the violation of universal values, others appear to be embedded in national parochialism and dangerous radical positions.